Consecutive interpreting techniques studies on intercultural communication of Zhuang Medicine culture from the perspective of speech act theory - Chenhua, Wei (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
This paper aims toÂ explore Consecutive Interpreting techniques needed to facilitate Intercultural Communication of Zhuang Medicine Culture from the Perspective of Speech Act Theory,based on ASEAN Guangxi International Workshop on TCM Zhuang and Yao Medicine. It is foundÂ that the Speech Act Theory can effectively guide the C-E International Zhuang Medicine Workshop classroom interpreting and contribute to better classroom communication. Meanwhile, the application of techniques such as semantic deverbalization, amplification and negation can facilitate imparting of Zhuang Medicine Culture knowledge.